We hope you enjoy our collection of funny math proofs, favorite math jokes and jokes about numbers. You may want to check out our algebra math jokes, calculus math jokes, geometry math jokes etc. on our Math Trivia page.

Related Topics:

Math Trivia, Math Jokes, Math Quotes

### A collection of Funny (or Flawed) Math Proofs

The above proof is incorrect because "Money is not the root of all evil". It is "The love of money that is the root of all evil" and of course "girls are not evil" (Proof by Majority Rule).

Both sides we will factorize. See?

Now each side contains a − b. [(a+b)(a − b) = b(a − b)]

We'll divide through by a

Minus b and olé

a + b = b. Oh whoopee! [a + b = b]

But since I said a = b

b + b = b you'll agree? [b + b = b]

So if b = 1

Then this sum I have done [1 + 1 = 1]

Proves that 2 = 1. Q.E.D.

The above proof is incorrect because when we take the square root we must be careful to include both the positive and negative roots. There should then be two possible answers (one of which is to be rejected).

Abbott & Costello prove that 7 times 13 = 28

Prove the manager wrong and get the job.

Ma and Pa Kettle prove that 25 divided by 5 is 14

You can use the free Mathway calculator and problem solver below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

Related Topics:

Math Trivia, Math Jokes, Math Quotes

**A Mathematical Proof that "Girls are Evil"**

1. “Girls require time and money”;

girls = time × money

2. “Time is money”:

time = money

3. So girls are money squared:

girls = money^{2}

4. ”Money is the root of all evil”:

money = \(\sqrt {evil} \)

5. So, girls are evil:

girls = \({\left( {\sqrt {evil} } \right)^2}\) = evil

The above proof is incorrect because "Money is not the root of all evil". It is "The love of money that is the root of all evil" and of course "girls are not evil" (Proof by Majority Rule).

**Prove that 2 = 1**

If a = b (so I say) [a = b]

And we multiply both sides by a

Then we'll see that a^{2} [a^{2} = ab]

When with ab compared

Are the same. Remove b^{2}. OK? [a^{2} − b^{2} = ab − b^{2}]

Both sides we will factorize. See?

Now each side contains a − b. [(a+b)(a − b) = b(a − b)]

We'll divide through by a

Minus b and olé

a + b = b. Oh whoopee! [a + b = b]

But since I said a = b

b + b = b you'll agree? [b + b = b]

So if b = 1

Then this sum I have done [1 + 1 = 1]

Proves that 2 = 1. Q.E.D.

Written by PeterW

(Just in case you're wondering - the above proof is incorrect because in step 5, we divided by (a - b) which is 0 since a = b)

Proof that $1 = 1 cent

$1 = 100 cents

= (10 cents)^{2}

= ($0.1)^{2}

= $0.01

= 1c

The above proof is incorrect because 100 cents = 10^{2} cents ≠ (10 cents)^{2}

A Proof that 0 = 1.

Abbott & Costello prove that 7 times 13 = 28

Prove the manager wrong and get the job.

Rotate to landscape screen format on a mobile phone or small tablet to use the **Mathway** widget, a free math problem solver that **answers your questions with step-by-step explanations**.

You can use the free Mathway calculator and problem solver below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

We welcome your feedback, comments and questions about this site or page. Please submit your feedback or enquiries via our Feedback page.